Profiling of Flavonoid Constituents in Sophora davidii Using UHPLC-Q-Exactive Orbitrap Mass Spectrometry and Evaluation of Antioxidant Activity - Shihan Qin; Xue Jiang; Shani Li; Qing Li; Jin Huang; Qingjiao He; Wei Cai (Journal of Chemistry)
The dried root of Sophora davidii Kom. ex Pavol (Leguminosae, family) is a folk medicine and has long been used for the treatment of various diseases, including cough, hematochezia, sore throat, and dysentery. In this study, UHPLC-Q-Exactive Orbitrap mass spectrometry investigations were applied to obtain the profiling of the flavonoids in S. davidii. Finally, 108 compounds were identified, and 85 of them were firstly reported. Then, the in vitro antioxidant activity and tyrosinase activity of S. davidii were investigated using the DPPH radical scavenging ability, hydroxyl radical scavenging, and copper-reducing ability method and by measuring the rate of tyrosinase-catalyzed L-dopa oxidation. To our knowledge, this is the first study of S. davidii’s antioxidant activity, anti-tyrosinase activity, and systematic characterization of flavonoids. The current study will be of support for the usage of S. davidii in the future development of the pharmaceutical industry.